Assessment of intracardiac flow dynamics for the evaluation of patients with different ventricular geometry. (14th October 2021) - Leo, I; Sabatino, J; Strangio, A; Maglione, M; Troilo, F; Loliva, G; Canino, G; Critelli, C; De Rosa, S; Indolfi, C
Abstract: Background: Over the last decades growing evidence have demonstrated the promising role of intracardiac flow dynamic analysis in evaluating cardiac performance. Diastolic forces contribute to the formation of vortices, complex structures capable of kinetic energy storage and responsible of a smoother transition of blood from left ventricular (LV) inlet to outlet. Change in shape and location of these structures has been related with cardiovascular disease and prognosis. Purpose: To investigate quantitative changes in vortices parameters in patients with different ventricular geometry. Methods: We enrolled 72 consecutive patients (age 66±11 years, 49 male, 68%) with LV concentric hypertrophy (CH, n=15), eccentric hypertrophy (EH, n=13), concentric remodeling (CR, n=15) and normal LV geometry (CTRL, n=29). Each patient underwent a complete echocardiographic examination and a non-invasive intracardiac fluid dynamic analysis by Color Vector Flow Mapping. A 3-chamber apical view with a frame rate between 22 and 25 Hz has been acquired and subsequently analyzed offline by a semi-automatic software obtaining the following parameters: vortex area (VA) (the ratio between the total vortex area and the left ventricular (LV) area); vortex length (VL) (the longitudinal length of the vortex relative to the total LV length; vortex depth (VD) (the distance of the vortex center from the LV base relative to the total LV long axis). Bland Altman Plot has been used to assess intra and inter-observer variability. Results: Mean VD was higher in CR, CH and EH compared to CTRL (p=0.013, p=0.001 and p=0.022, respectively). Moreover, CH showed higher VL (p=0.006) and larger VA (p=0.012) compared to CTRL. A similar trend was noticed in EH patients, despite did not reach statistical significance (p=0.21 and p=0.07 for VA and VL respectively). No significative differences in vortices parameters have been observed between CH and EH. Conclusion(s): This is the first study providing quantitative echocardiographic parameters of vortex location and morphology in different LV geometries. Higher values of VD were found in CR, CH and EG. Quantitative intra dynamic fluid assessment was feasible and reliable in the whole population and could provide additional information to the standard echocardiographic examination. Funding Acknowledgement: Type of funding sources: None.